Analisis Reformasi Birokrasi Pada Sekretariat Daerah Kabupaten Tulungagung - Arifin, Dwi; Laksono, Sonny SM (Otonomi, 2024)
The purpose of this research is to describe the execution of bureaucratic reforms and analyze the driving and implementation of bureaucratic reforms in the secretariat area of the Tulungagung district. In this study, it uses a qualitative method. The study was focused on how bureaucratic reforms were performed on the secretariat area of the Tulungagung district by looking at indicators of 8 areas of change that became the goal of bureaucratic reform. With the data collection technique of interviews, The observation and literature resulting from this research is the execution of bureaucratic reforms in the Tulungangang district is good enough as well as to realize the red tape advanced into world-class bureaucracy required to act on bureaucratic reforms with more exposures and impacts than in the process. A barrier factor in the attainment of bureaucratic reform due to a lack of strong leadership and inability to design and apply policy.